Architecture of Computing Systems - ARCS 2011 24th International Conference, Como, Italy, February 24-25, 2011. Proceedings - Berekovic, Mladen; Fornaciari, William; Brinkschulte, Uwe.; Silvano, Cristina; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 24th International Conference on Architecture of Computing Systems, ARCS 2011, held in Lake Como, Italy, in February 2011. The 22 revised full papers presented in seven technical sessions were carefully reviewed and selected from 62 submissions. The papers are organized in topical sections on customization and application specific accelerators; multi/many-core architectures; adaptive system architectures; processor architectures; memory architectures optimization; organic and autonomic computing; network-on-chip architectures.
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Computer network architectures; Software engineering; Operating systems (Computers).; Information storage and retrieval systems; Information systems; Electronic books